TRANSPORT RATES OF Na^+, Cl^-, NO_3^- AND SO_4^<2-> BY DRIFTING SNOW AT MIZUHO STATION, ANTARCTICA - オサダ, カズオ; ヒグチ, ケイジ; OSADA, Kazuo; HIGUCHI, Keiji (National Institute of Polar Research, 1990)
P(論文) Transport rates of Na^+, Cl^-, NO_3^- and SO_4^<2-> by drifting snow are estimated to evaluate the contribution to material transport process at Mizuho Station, Antarctica. Daily transport rates of Na^+ and Cl^- by drifting snow in winter are about 3 times as large as their transport rates in summer, whereas daily transport rates of NO_3^- and SO_4^<2-> in winter are two thirds of those in summer. Transport rates of chemical constituents by ice flow are also estimated to compare with the results by drifting snow. Transport rates of chemical constituents by drifting snow comprise between 9% and 18% of the amount transported by ice flow. This result indicates that not only ice flow but also drifting snow has an important role for transport of chemical constituents toward the coastal region. Differences in NO_3^- and SO_4^<2-> concentrations (in μg・l^<-1>) between ice core (56 and 51) and snow drift in summer (315 and 199,respectively) suggest that deposition of snow layer in summer probably does not occur at altitudes from 2000m to 3000m in the katabatic wind region. Annual transport of sulfate by drifting snow across the 2000m contour is estimated to compare with the sulfate amount transported through the whole Antarctic atmosphere estimated by R. J. DELMAS (Nature, 299,677,1982). Amount of sulfate transport (1.4×(10)^6 kg・(yr)^<-1>) by drifting snow toward the coastal region below altitude 2000m is three orders smaller than that through the whole Antarctic atmosphere. departmental bulletin paper